2003
DOI: 10.1007/s00792-003-0327-6
|View full text |Cite
|
Sign up to set email alerts
|

α-Amylase activity from the halophilic archaeon Haloferax mediterranei

Abstract: The halophilic archaeon Haloferax mediterranei is able to grow in a minimal medium containing ammonium acetate as a carbon and nitrogen source. When this medium is enriched with starch, alpha-amylase activity is excreted to the medium in low concentration. Here we report methods to concentrate and purify the enzyme. The relative molecular mass of the enzyme, determined by gel filtration, is 50 +/- 4 kDa, and on SDS-PAGE analysis a single band appeared at 58 kDa. These results indicated that the halophilic alph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(58 citation statements)
references
References 39 publications
1
55
0
Order By: Relevance
“…Many -amylases have been identified in various organisms, but those from extremely halophilic archaea are less well-known. To date, a maltotrioseforming -amylase from Natronococcus amylolyticus, 30) an -amylase from Haloferax mediterranei, 31) and an -amylase from Haloarcula hispanica 32) have been reported. These four -amylases, including MalA, are equally halophilic.…”
Section: Characterization Of Recombinant Malamentioning
confidence: 99%
“…Many -amylases have been identified in various organisms, but those from extremely halophilic archaea are less well-known. To date, a maltotrioseforming -amylase from Natronococcus amylolyticus, 30) an -amylase from Haloferax mediterranei, 31) and an -amylase from Haloarcula hispanica 32) have been reported. These four -amylases, including MalA, are equally halophilic.…”
Section: Characterization Of Recombinant Malamentioning
confidence: 99%
“…However, enzyme production were stable at 60°C, but the enzyme stability was better than that of other researcher findings (Tan et al, 2008;Prakash et al, 2009). Therefore, according to the findings it should be noted that the amylase producing halothermophilic strains might be called halophilic because the halophilic enzymes are usually inactive when the NaCl or KCl concentration is less than 2 M (Mader et al, 2000) as Pomares et al (2003) showed that the optimum salt concentration for amylase production of Haloferax mediterranei was 3 M NaCl. Therefore, this halophilic stability and adaptation of halothermophilic strains with capability to produce amylase (higher than the other halophilic strains than that of other researcher isolates) suggested that, these strains could be a good choice for some biotechnological application.…”
Section: Discussionmentioning
confidence: 90%
“…Some halophilic amylases from Archaea have been characterized [51][52][53][54][55]. Most of them retain their activity at high temperatures.…”
Section: Glycosyl Hydrolasesmentioning
confidence: 99%
“…Most of them retain their activity at high temperatures. For example, the haloarchaeon H. mediterranei secretes an α-amylase showing optimum temperature between 50 and 60°C, but it retains 65% of the maximum activity at 80°C [55]. H. mediterranei also has a monomeric extracellular cyclodextrin glycosyltransferase working optimally at 55°C and 1.5 M NaCl, but it is active even at low salt concentrations as 0.5 M NaCl (retaining 65% of its activity) [56].…”
Section: Glycosyl Hydrolasesmentioning
confidence: 99%